2020
DOI: 10.3390/ani10091647
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Load of the Teat Apex Skin and Associated Factors at Herd Level

Abstract: In order to reduce antimicrobial treatment and prevent environmental mastitis, the aim of the present study was to investigate associations between herd level factors and microbial load on teat ends with environmental mastitis pathogens. Quarterly farm visits of 31 dairy farms over a one-year period were used for statistical analysis. During each farm visit, teat-skin swabs, bedding and air samples were taken and management practices and herd parameters were documented. Total mesophilic bacteria, esculin-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
4
10
0
Order By: Relevance
“…The CC in our finding agrees with reports from central Ethiopia [53] and Brazil [15]. In line with our findings, dirty barns [50], dirty cows [5,56] and soiled udder and teats [16] were reported to be associated with increased CC in bulk milk. In this study, the use of warm water to clean teats was related to low CC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The CC in our finding agrees with reports from central Ethiopia [53] and Brazil [15]. In line with our findings, dirty barns [50], dirty cows [5,56] and soiled udder and teats [16] were reported to be associated with increased CC in bulk milk. In this study, the use of warm water to clean teats was related to low CC.…”
Section: Discussionsupporting
confidence: 92%
“…These conditions might have been resulted in soiling of the udder and teats, which might ultimately contaminate milk [49]. Udder and teat hygiene are the major factors associated with microbial contamination in bulk milk [15,50]. Pre-and/or postmilking teat disinfection were reported to reduce the bacterial load on teat skin and were found to be the most effective practice against environmental bacteria [8,51].…”
Section: Discussionmentioning
confidence: 99%
“…and Enterobacter aerogenes ) also cause mastitis. The endotoxins contained in the bacterial cell wall have a pathogenic effect (Hohmann et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This could be a possible explanation for the worse HMR in herds using moist teat cleaning devices. On the other hand, Hohmann et al [ 36 ] found no increase in bacterial loads when more than one cow was cleaned per wipe. However, efficiency of teat cleaning not only depends on the device used for cleaning, but also on how thorough the person is when cleaning the teat.…”
Section: Discussionmentioning
confidence: 99%